Crecimiento, mortalidad y tasa de explotación de Priacanthus arenatus (Perciformes: Priacanthidae), en la pesca de arrastre del nororiente de Venezuela - Toledo, J.; Mendoza, J.; Marcano, L. (Revista de Biología Tropical, 2000)
We analyzed growth; mortality and exploitation rate of Priacanhus arenatus, captured by the shrimp trawling fishery (1989-1996), in northeastern Venezuela. The growth coefficient (K) and the asymptotic length (L8) were estimated by length-frequency data using the Battacharya method and other routines of the FISAT program. Total mortality (Z) and exploitation (E) rates were obtained by length-converted catch curve analysis, based on length frequency data, and the Berveton and Holt’s yield per recruit model, respectively. The mean growth parameters L and K were estimated as 474.7 mm and 0.69 year-1, respectively. Mean total mortality was 4.03 and the exploitation rate range was 0.70-0.80. Results indicated that the population is overexploited.